Perancangan Aplikasi Mobile Berbasis Android Untuk Transaksi Dan Manajemen Stok Di Warung Sembako - Fadilla, Fadlan Arsy; Windyasari, Vina Septiana; Sukrim, Sukrim (Universitas Islam Syekh Yusuf Tangerang, 2025)
Grocery stalls still manage transactions and stock conventionally, which is prone to errors and inefficient. Therefore, this study aims to design and develop an Android-based mobile application to support sales transactions, stock management, and digital transaction recording, which also includes a Stock Coverage Days feature that can be used to predict how long a product’s stock will last. The development was carried out using the Extreme Programming (XP) method to enable fast and flexible system development, and the application was built using the Flutter framework with the Dart programming language, as well as utilizing Supabase as the backend and real-time database. The testing results show that the application can improve transaction efficiency by 44.13% faster compared to conventional methods.